The spy who would be tsar the mystery of Michal Goleniewski and the far-right underground - Coogan, Kevin (Routledge, Taylor & Francis Group, 2022)
"Michal Goleniewski was one of the Cold War's most important spies but has been overlooked in the vast literature on the intelligence battles between the Western Powers and the Soviet Bloc. Renowned investigative journalist Kevin Coogan reveals Goleniewski's extraordinary story for the first time in this biography. Goleniewski rose to be a senior office in the Polish intelligence service, a position which gave him access to both Polish and Russian secrets. Disillusioned with the Soviet Bloc, he made contact with the CIA, sending them letters containing significant intelligence. He then decided to defect and fled to America in 1961 via an elaborate escape plan in Berlin. His revelations led to the exposure of several important Soviet spies in the West including the Portland spy ring in the UK, the MI6 traitor George Blake, and a spy high up in the West German intelligence service. Despite these hugely important contributions to the Cold War, Goleniewski would later be abandoned by the CIA after he made the outrageous claim that he was actually Tsarevich Alexei Nikolaevich of Russia - the last remaining member of the Romanov Russian royal family and therefore entitled to the lost treasures of the Tsar. Goleniewski's increasingly fantastical claims led to him becoming embroiled in a bizarre demi-monde of Russian exiles, anti-communist fanatics, right-wing extremists and chivalric orders with deep historical roots in America's racist and antisemitic underground. This fascinating and revelatory biography will be of interest to students and researchers of the Cold War, intelligence history and right-wing extremism as well as general readers with an interest in these intriguing subjects"--
Keywords: Goleniewski, Michał -- 1922-1993; Goleniewski, Michal / 1922-1993; Intelligence service / Poland; Cold War; Spies / Poland / Biography; Defectors / Poland / Biography; Defectors / United States / Biography; Right-wing extremists / Biography; Defectors; Intelligence service; Right-wing extremists; Spies; Poland; United States; Biographies; Biografie